Endobronchial ultrasound-guided transbronchial fine needle aspiration: synopsis and prospects - V. I. Kobylyansky (Фундаментальная и клиническая медицина)
Despite the high informativeness of minimally invasive methods for assessing respiratory system, lung tissue biopsy is often required to verify the diagnosis. Conventional methods include surgical biopsy, which considered as the gold standard but is associated with significant complications and mortality, and transbronchial biopsy, a less invasive but substantially less informative method. The most informative and novel approach is endobronchial ultrasoundguided transbronchial fine needle aspiration (EBUS-TBNA), which significantly surpasses forceps biopsy. Here I focus on EBUS-TBNA, highlighting its capabilities, the future prospects, expedient technical solutions in certain of its modification and the lack thereof in others, and approaches for the standardization.